2010
DOI: 10.3109/07420520903502242
|View full text |Cite
|
Sign up to set email alerts
|

Obesity and High Blood Pressure of 12-Hour Night Shift Female Clean-Room Workers

Abstract: The 12 h shift schedule is widely used in clean rooms for electronic semiconductor production in Taiwan. This study investigated the associations of obesity and metabolic syndrome (MetS) components among women working in a semiconductor manufacturing factory in North Taiwan. Workers were divided into four groups according to their work schedules and duties (i.e., office workers, day workers, fixed 12 h day shift, and fixed 12 h night shiftworkers). The subjects comprised 1838 women who voluntarily attended a h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
77
5
5

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(93 citation statements)
references
References 38 publications
6
77
5
5
Order By: Relevance
“…Lowden et al (2010) discussed a range of possible dietary mechanisms that may underlie the link between shiftwork and the symptoms of metabolic syndrome. They noted that several studies have shown associations between shiftwork and obesity (e.g., Chen et al, 2010;Gangwisch et al, 2005;Vorona et al, 2005), although not all findings have supported such a link. The causal factors underlying the association are not well established, although restricted sleep that is common among shiftworkers has been identified as a potentially important issue (Lowden et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Lowden et al (2010) discussed a range of possible dietary mechanisms that may underlie the link between shiftwork and the symptoms of metabolic syndrome. They noted that several studies have shown associations between shiftwork and obesity (e.g., Chen et al, 2010;Gangwisch et al, 2005;Vorona et al, 2005), although not all findings have supported such a link. The causal factors underlying the association are not well established, although restricted sleep that is common among shiftworkers has been identified as a potentially important issue (Lowden et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…have been conducted in specific workplace settings, primarily restricted to individuals employed in single industries, 7,8,[10][11][12][13][14][15]17,19,20,23,24,26,27 with only a few population-based studies, especially among men. 4,18 As a result, assessment of shift work exposure has been limited, with most studies examining only one specific shift schedule or pattern.…”
Section: Highlightsmentioning
confidence: 99%
“…Previous studies have clearly shown that shiftwork is associated with chronic health problems, for example, mental health disorders (Bara el al., 2009;Driesen et al, 2009), cardiovascular disease (Puttonen et al, 2010), and the metabolic syndrome (Chen et al, 2010;Karlsson et al, 2003;Padilha et al, 2009). These health problems are often discussed in the context of elevated psychosocial stress arising from a mismatch between job demand and job control (Alves et al, 2004;Bara el al., 2009;Rystedt et al, 2008;Thomas et al, 2009), which can result in pronounced levels of the stress hormone cortisol (Rystedt et al, 2008).…”
Section: Introductionmentioning
confidence: 99%